Hotel Spa managers’ perceptions of service quality in Greece - Bakirtzoglou, Panteleimon; Vryoni, Spyridoula; Ioannou, Panagiotis (Serbian Journal of Management, 2018)
The purpose of the present study was to investigate which dimensions of service quality are most important to Hotel Spa managers for their customers’ satisfaction in Greece. Thirty three (n=33) Hotel Spa managers in Greece volunteered to participate in the present study. Measurements included the use of the SERVQUAL instrument (Parasuraman et al., 1988) to measure perceptions of service quality. Factor Analysis (principal component) with Varimax rotation was used to identify the predictive variables of managers’ perceptions. The results showed that three variables and four items of SERVQUAL model were the most predictive variables of managers’ perceptions. Factors were labeled as follows: Responsiveness, Reliability and Tangibles. Items were labeled as follows: timeliness of Hotel Spa’s staff, employees’ professionalism, food and beverages and providing promptness service implementation. Those three factors and four items explained Hotel Spa managers' perceptions at the percentage of 50.97%. In conclusion, human (responsiveness and reliability) and environmental (tangibles) factors of service quality are important parameters for Hotel Spa managers in Greece, when they design marketing services aiming to improve their customers’ satisfaction.